Pragmatic Analysis Of The Phatic Speech Act Of Greeting - Akramova, Dilnoza Nu'monjonovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article is focused on the greeting type of phatic speech acts, the problem of its classification according to semantic features, and discusses the three main elements of the greeting speech act.